2014
DOI: 10.1186/1472-6963-14-384
|View full text |Cite
|
Sign up to set email alerts
|

Health care provider perspectives on pregnancy and parenting in HIV-positive individuals in South Africa

Abstract: BackgroundWithin the health system, limited attention is given to supporting the fertility and parenting desires on HIV-positive people. In this study, we explore health care providers’ knowledge and perspectives on safer conception and alternate parenting strategies for HIV-positive people.MethodsBetween November 2007 and January 2008, in-depth interviews were conducted with 28 health care workers involved in providing HIV and/or antiretroviral services at public sector clinics in Cape Town, South Africa. Vie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 28 publications
0
37
0
2
Order By: Relevance
“…Earlier research suggested that providers tended to focus on negative outcomes of childbearing for PLHIV, creating reluctance to advise condomless sex or other safer conception methods for PLHIV and their partners [6,4244]. However, recent studies indicate that providers increasingly empathize with reproductive goals of PLHIV, recognize reduced perinatal transmissions following eMTCT interventions, acknowledge the need for safer conception training and care and show greater awareness of safer conception methods [4550]. In order to cement this shift, widespread promotion of a reproductive-rights based patient care approach is required.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier research suggested that providers tended to focus on negative outcomes of childbearing for PLHIV, creating reluctance to advise condomless sex or other safer conception methods for PLHIV and their partners [6,4244]. However, recent studies indicate that providers increasingly empathize with reproductive goals of PLHIV, recognize reduced perinatal transmissions following eMTCT interventions, acknowledge the need for safer conception training and care and show greater awareness of safer conception methods [4550]. In order to cement this shift, widespread promotion of a reproductive-rights based patient care approach is required.…”
Section: Discussionmentioning
confidence: 99%
“…Couples who are living with HIV and do not desire to get pregnant and want to use a permanent method of family planning must be able to easily access tubal ligation and vasectomy methods; they should be trained and advised about using these methods but they must not be forced to use one of these methods. Healthcare providers' training, as well as systematizing the assessment of reproduction intention of PLHIV seem necessary to meet the sexual and reproductive health needs of this sub population in the communities (31). They also should consider that the contraceptive methods should be acceptable by PLHIV.…”
Section: Unintended Pregnancy and Safe Abortion Servicesmentioning
confidence: 99%
“…Numerous studies have shown that health care providers often refrain from asking HIV-positive individuals, especially men, about their fertility desires [61]. Among many clinicians there is low awareness of safer conception options and that HIV serodiscordance can be maintained in a couple [61].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that health care providers often refrain from asking HIV-positive individuals, especially men, about their fertility desires [61]. Among many clinicians there is low awareness of safer conception options and that HIV serodiscordance can be maintained in a couple [61]. There is also a perception that in the pre-ART period couples do not consider fertility issues [61], despite the fact that fertility planning is critical in this group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation